Severe kerion celsi effectively treated with skin debridement and antifungals - Putranti, Ismiralda Oke; Primanita, Citra (Journal of General - Procedural Dermatology and Venereology Indonesia, 2018)
Background: Kerion celsi is a severe inflamed deep abscesses form of tinea capitis which mostly occurs in children population. Despite good regular treatment with antifungals, the prognosis of kerion celsi is poor with scarring alopecia. Case Illustration: A 5-year-old boy had history of an alopecia with locally large painful oedema on his scalp a month before treatment. From the physical examination, a painful large area with alopecia was found with abscess covered by thick crust. Pull test showed hair breakage and right retro-auricular lymphatic nodes enlargement was also found. Endo-ectothrix spores were positive in potassium-hydroxide examination and the culture showed colony of Trichophyton mentagrophytes. A surgical debridement was performed to remove the thick crust covering the abscess with alopecia and followed by application of normal saline gauze dressing and terbinafine cream on the top of the lesion for 6 weeks. Systemic micronized griseofulvin was also administered for 6 weeks. Combination treatment of debridement-topical and systemic antifungal gave a good result without scarring alopecia. Discussion: Kerion celsi was diagnosed based on clinical findings and mycological examination. From the laboratory examination, a dermatophyte fungal infection was found. Skin debridement was performed to create a good environment for topical antifungal application and wound healing, with 20mg/kg bodyweight of systemic griseofulvin administered as the first line therapy for tinea capitis. A good prognosis was achieved after those treatments combination. Conclusion: In this case, combination between skin debridement with topical and systemic antifungals gave a better result in treating kerion celsi.